2005
DOI: 10.1063/1.1989447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-deposition annealing in O2 on the electrical characteristics of LaAlO3 films on Si

Abstract: LaAlO 3 films were deposited on p-type Si(100) by sputtering from a LaAlO3 target. C×V characteristics were determined in nonannealed and O2-annealed capacitors having LaAlO3 films as dielectric and RuO2 as top electrode. Thermal annealing in O2 atmosphere reduced flat band voltage to acceptable values for advanced Si-based devices. O16–O18 isotopic substitution was characterized by Rutherford backscattering spectrometry and nuclear resonant reaction profiling. Chemical analysis of the films was accomplished b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…However, HfO 2 layers on Si tend to possess a SiO 2 -based interfacial layer which limits the attainment of very low effective oxide thickness (EOT). Future scaling calls for lower EOTs, and for this a leading candidate is LaAlO 3 [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HfO 2 layers on Si tend to possess a SiO 2 -based interfacial layer which limits the attainment of very low effective oxide thickness (EOT). Future scaling calls for lower EOTs, and for this a leading candidate is LaAlO 3 [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…But a key advantage of LaAlO 3 is that it has much lower atomic diffusion rates than HfO 2 , which limits the growth of any subcutaneous SiO 2 layer between the Si channel and the oxide [12][13][14]. Recently amorphous LaAlO 3 gate stacks with an EOT of only 0.3 nm were achieved [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Sm 2 TiO 5 film performed at 700 • C possessed a smooth surface (0.518 nm), whereas the one annealed at 900 • C showed a rough surface (2.632 nm). We suggest that this behavior is due to an increased self-diffusion of samarium, titanium and oxygen during high-temperature annealing leading to the enhancement of the clustering of grains, thus increasing the sur- face roughness of the Sm 2 TiO 5 film [20]. The surface roughness of Sm 2 TiO 5 film annealed at different PDA temperatures reflects on the corresponding the intensity and orientation of the diffraction peak, as shown in Fig.…”
Section: Structural Propertiesmentioning
confidence: 83%
“…In recent years, the samarium oxide (Sm 2 O 3 ) films have been considered as potential gate insulators because of their reasonably high relative permittivity (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), good thermal stability, and large conduction band offset (>2 eV) [15]. We have previously reported that a Sm 2 O 3 gate dielectric exhibited excellent electrical characteristics such as a small equivalent oxide thickness, low gate leakage current, and small frequency dispersion [16].…”
Section: Introductionmentioning
confidence: 99%
“…There are several deposition techniques for the high-k oxide insulators, such as sputtering-deposition [15], molecular beam evaporation [16], chemical vapor deposition [17], pulsed laser deposition [18], and atomic layer deposition (ALD) [19,20]. Among them, the ALD technique is regarded as a preferred method for deposition of uniform oxide insulator in a layer-by-layer mode [21].…”
Section: Introductionmentioning
confidence: 99%